Analysis of Administrative Services on Organizational Governance through Managerial Performance at the Human Resources Development Agency of South Sulawesi Province - Ansar Amir; Mardihang Haruna (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Human resources are one of the very important factors and cannot be separated from an organization. Today, human resources are no longer viewed only as resources but are capital or asset in an organization. The purpose of this study is to analyze the effect of administrative services on managerial performance, analyze the effect of administrative services on organizational governance, and analyze the indirect influence of administrative services through managerial performance on the organizational governance of BPSDM South Sulawesi Province. The study was carried out at the BPSDM of South Sulawesi Province with a sample based on the Slovin formula determined by 322 respondents. The analysis technique used is the Structural Equation Model (SEM) contained in the AMOS v. 22 program. The results of the study using path analysis were obtained as follows: First, the implementation of administrative services affects the governance of the BPSDM organization. Second, managerial performance practices have not been able to encourage the implementation of administrative services in influencing the governance of the BPSDM organization. The results of the test showed that administrative services had a positive effect on organizational governance variables. This means that the implementation of administrative services can improve the implementation of organizational governance. The better the implementation of administrative services, the organizational governance within the scope of BPSDM Of South Sulawesi Province will increase